Formulation, characterisation and optimisation of self-nanoemulsifying drug delivery systems (SNEDDS) loaded with artemether and lumefantrine - Mudyahoto, Tsitsi (Rhodes University, Faculty of Pharmacy, Pharmacy, 2018)
Expected release date-April 2020
Keywords: Uncatalogued